Cube Roots Again!

Algebra Level 3

Find the value of ( 2 ω ) ( 2 ω 2 ) ( 2 ω 10 ) ( 2 ω 11 ) . (2-\omega)(2-\omega^2)(2-\omega^{10})(2-\omega^{11}).

Details and Assumptions:

ω \omega is a non-real cube root of unity.


The answer is 49.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Discussions for this problem are now closed

As ω \omega is the cube root of unity.

ω 10 = ω , ω 11 = ω 2 \Rightarrow \omega^{10} = \omega, \omega^{11} = \omega^2

Then, ( 2 ω ) ( 2 ω 2 ) ( 2 ω 10 ) ( 2 ω 11 ) (2- \omega)(2- \omega^2)(2- \omega^{10})(2- \omega^{11})

= ( ( 2 ω ) ( 2 ω 2 ) ) 2 = ((2- \omega)(2- \omega^2))^2

Now, since ( x ω ) ( x ω 2 ) = x 2 + x + 1 (x- \omega)(x- \omega^2) = x^2 + x + 1 ,

= ( 2 2 + 2 + 1 ) 2 = (2^2 + 2 +1)^2

= 7 2 = 49 = 7^2 = \boxed{49} .

I liked how you use ( x ω ) ( x ω 2 ) = x 2 + x + 1 ( x - \omega) ( x - \omega^2 ) = x^2 + x + 1 . In cases like this, evaluating f ( x ) f(x) and then substituting in x = 2 x = 2 , is an easier approach than trying to figure out f ( 2 ) f(2) directly.

Calvin Lin Staff - 6 years, 6 months ago
Sandeep Bhardwaj
Dec 8, 2014

ω \omega being cube-root of unity. ( 1 ) \left( \neq 1 \right) , ω = 1 + 3 i 2 \omega=\dfrac{-1+\sqrt{3}i}{2} or ω = 1 3 i 2 \omega=\dfrac{-1-\sqrt{3}i}{2}

Here we will use the cute property of ω \omega : 1 + ω + ω 2 = 0 \boxed{1+\omega+\omega^2=0} So, ( 2 ω ) ( 2 ω 2 ) ( 2 ω 10 ) ( 2 ω 11 ) (2-\omega)(2-\omega^2)(2-\omega^{10})(2-\omega^{11})

= ( 2 ω ) ( 2 ω 2 ) ( 2 ω ) ( 2 ω 2 ) \quad = (2-\omega)(2-\omega^2)(2-\omega)(2-\omega^2) ( b e c a u s e ω 10 = ω , ω 11 = ω 2 ) \left( because \ \omega^{10}=\omega, \omega^{11}=\omega^2 \right)

= ( ( 2 ω ) ( 2 ω 2 ) ) 2 \quad = \left( (2-\omega)(2-\omega^2) \right)^2

= ( 4 2. ω 2. ω 2 + ω 3 ) 2 \quad = \left( 4-2.\omega-2.\omega^2+\omega^3 \right)^2

= ( 5 2. ω 2 ω 2 ) 2 \quad =\left( 5-2.\omega-2\omega^2 \right)^2 ( b e c a u s e ω 3 = 1 ) \left( because \ \omega^3=1 \right)

= ( 7 2 2. ω 2. ω 2 ) 2 \quad =\left( 7-2-2.\omega-2.\omega^2 \right)^2

= ( 7 0 ) 2 = 49 \quad = \left( 7-0 \right)^2=\boxed{49}

Awesome solution, I will add more to your solution, demonstrating the cute property : 1 + ω + ω 2 = 0 \boxed{1+\omega+\omega^2=0}

Let ω 3 = 1 \omega^3=1

ω 3 1 = 0 \omega^3-1=0

( ω 1 ) ( ω 2 + ω + 1 ) = 0 (\omega-1)(\omega^2+\omega+1)=0

So, or ω = 1 \omega=1 or ω 2 + ω + 1 = 0 \omega^2+\omega+1=0

Since ω \omega can't be 1

1 + ω + ω 2 = 0 \boxed{1+\omega+\omega^2=0}

Pedro Souto - 6 years, 6 months ago
Ariel Gershon
Dec 10, 2014

First since w 3 = 1 w^3 = 1 , we can rewrite the expression as ( 2 w ) 2 ( 2 w 2 ) 2 (2-w)^2(2-w^2)^2 .

Since w , w 2 , 1 w, w^2, 1 are the three roots of the equation x 3 1 = 0 x^3-1=0 , then that means ( x 1 ) ( x w ) ( x w 2 ) = x 3 1 (x-1)(x-w)(x-w^2) = x^3 - 1 . If we let x = 2 x = 2 , we get ( 2 1 ) ( 2 w ) ( 2 w 2 ) = 2 3 1 (2-1)(2-w)(2-w^2) = 2^3 - 1 ( 2 w ) ( 2 w 2 ) = 7 (2-w)(2-w^2) = 7 ( 2 w ) 2 ( 2 w 2 ) 2 = 49 (2-w)^2(2-w^2)^2 = \boxed{49}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...